Chuanxiong improves angiogenesis via the PI3K/AKT/Ras/MAPK pathway based on network pharmacology and DESI-MSI metabolomics - Cheng, Xue-hao; Yang, Xue-xin; Cui, He-rong; Zhang, Bei-bei; Chen, Ke-dian; Yang, Xiao-yun; Jiao, Jing-yi; Du, Ya-wen; Zhang, Qi; Zheng, Jia-xin; Xie, Wei; Li, Fei-fei; et al. (Frontiers in Pharmacology, 2023)
Introduction: Chuanxiong, a traditional Chinese medicine, has been proved to treat a variety of cardiovascular and cerebrovascular diseases by promoting angiogenesis. However, the mechanisms of Chuanxiong’s pro-angiogenesis is currently unknown. This study aimed to uncover the effect and mechanisms of Chuanxiong promoting angiogenesis in vivo and in vitro. Methods: First, potential targets were predicted by network pharmacology analysis, and PPI network was established and the pathways were enriched. Then, the chorioallantoic membrane test on quails was applied to assess the proangiogenic effects in vivo. As well, to evaluate the effects in vitro, real-time PCR, western blot analysis, the scratch test, and the tube formation experiment were used. Subsequently, the major metabolic pathways were analyzed using non-targeted metabolomics. Results: As a result of network pharmacological analysis, 51 collective targets of Chuanxiong and angiogenesis were identified, which are mainly associated with PI3K/AKT/Ras/MAPK pathway. And the biological verification results showed that Chuanxiong could increase the vessel numbers and vessel area in qCAM models. Meanwhile, Chuanxiong contributed to HUVEC proliferation, tube formation, migration, by encouraging scratch healing rates and boosting tube branch points. In addition, the levels of VEGFR2, MAPK and PI3K were elevated compared to the control group. The western blot analysis also confirmed Chuanxiong could promote an increase in AKT, FOXO1 and Ras. Furtheremore, metabolomic results showed that the proangiogenic effect of Chuanxiong is associated with glycine, serine and threonine metabolism. Discussion: In conclusion, this study clarified that Chuanxiong could promote angiogenesis in vivo and in vitro via regulating PI3K/AKT/Ras/MAPK pathway.